CLARIFICACIÓN DE VINAZAS PROVENIENTES DE LA INDUSTRIA DE LA “RAICILLA”, MEDIANTE EL USO DE HIDROGELES - Maribel Arrizón Fregozo; Nestor García Ramírez; Jorge Alberto Cortes Ortega; Juan Carlos Sánchez Díaz (Química Nova)
In this work, the clarification process of vinasse from the “raicilla” industry produced in the municipality of Mascota, Jalisco, Mexico is presented. Acrylamide and acrylamide/methacrylic acid hydrogels were synthesized, with a water/monomer ratio of 90:10 by mass. Subsequently, each xerogel sample was loaded with cobalt, copper or nickel ions. The hydrogels loaded with each metal were placed in NaOH 0.1 M solution, so the OH- ions penetrated the hydrogel and reacted with the metal ions, forming the corresponding hydroxide. Then the hydrogels loaded and swollen in the NaOH solution were placed in the vinasse for two days. After this time, a new hydrogel was placed and left for two more days, with which the intensity of the color of the vinasse decreased, as the process was repeated. In all cases, the treated vinasse was clarified, without significant changes in volume, indicative that the hydrogel no longer absorbs solution. This opens up the possibility of using this method for the clarification of vinasse from “raicilla” industry, through prior feasibility studies in efficiency, reuse of hydrogel, costs and technological development.